THE EFFECT OF THE AVAILABILITY OF SPORTS FACILITIES AND SOCIO-ECONOMIC CONDITIONS ON SPORTS PARTICIPATION - Nafsa, Milda Asyifa; Ma’mun, Amung (ASEAN Journal of Sport for Development and Peace, 2021)
There are several factors that lead to increased sports participation, such as sports facilities and socio-economic conditions. However, these factors have not been able to be optimized properly considering the relatively low sports participation in Indonesia. Thus, this study focuses on studies to determine the relationship between the availability of sports facilities and socio-economic conditions with the community participation rate in sports. The data used is secondary data obtained from the official website of the Badan Pusat Statistik (BPS), namely www.bps.go.id. The variables in this study are sports facilities, household expenditure for food needs, good road conditions, school participation status and internet access. This study used the ex post facto method and was processed using SPSS version 25 software using Multiple Regression Analysis. The results showed that 70 percent of the diversity of the community participation variables in sports could be explained by the variable availability of facilities and socio-economic conditions, while the remaining 30 percent was by variables outside the model. In addition, the F value in the Anova table shows a number α = 0.05, so it can be concluded that simultaneously the influence model between the availability of sports facilities and socio-economic conditions on sports participation is statistically significant. Partially, each variable included in the model also has a statistically significant effect, except for the variable school participation status. This research is expected to be used as a reference for policy makers in planning development and designing sports policies, especially in increasing sports participation in Indonesian.